Autophagic degradation of KAT2A/GCN5 promotes directional migration of vascular smooth muscle cells by reducing TUBA/α-tubulin acetylation. Issue 10 (2nd October 2020) - Ouyang, Changhan; Mu, Jing; Lu, Qiulun; Li, Jian; Zhu, Huaiping; Wang, Qilong; Zou, Ming-Hui; Xie, Zhonglin
ABSTRACT: Macroautophagy/autophagy, a fundamental process for degradation of macromolecules and organelles, occurs constitutively at a basal level and is upregulated in response to stress. Whether autophagy regulates protein acetylation and microtubule stability in vascular smooth muscle cells (VSMCs) migration, however, remains unknown. Here, we demonstrate that the histone acetyltransferase KAT2A/GCN5 (lysine acetyltransferase 2) binds directly to the autophagosome protein MAP1LC3/LC3 (microtubule associated protein 1 light chain 3) via a conserved LC3-interacting region (LIR) domain. This interaction is required for KAT2A sequestration in autophagosomes and degradation by lysosomal acid hydrolases. Suppression of autophagy results in KAT2A accumulation. KAT2A functions as an acetyltransferase to increase TUBA/α-tubulin acetylation, promote microtubule polymerization and stability, ultimately inhibiting directional cell migration. Our findings indicate that deacetylation of TUBA and perturbation of microtubule stability via selective autophagic degradation of KAT2A are essential for autophagy-promoting VSMC migration. Abbreviations: ACTB: actin beta; ATAT1: alpha tubulin acetyltransferase 1; ATG: autophagy-related; BECN1: beclin 1; CQ: chloroquine; FBS: fetal bovine serum; GST: glutathione S-transferase; H4K16ac: histone H4 lysine 16 acetylation; HASMCs: human aortic smooth muscle cells; HBSS: Hank's buffered salt solution; HDAC6: histone deacetylase 6; hMOF: human males absent on the first; IP: immunoprecipitation; KAT2A/GCN5: lysine acetyltransferase 2A; Lacta: lactacystin; LIR: LC3-interaction region; MAP1LC3: microtubule associated protein 1 light chain 3; MEFs: mouse embryonic fibroblasts; MTOC: microtubule-organizing center; PE: phosphatidylethanolamine; PtdIns3K: class III phosphatidylinositol 3-kinase; RUNX2: runt-related transcription factor 2; SIRT1: sirtuin 1; SIRT2: sirtuin 2; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like autophagy activating kinase 1; VSMCs: vascular smooth muscle cells; WT: wild-type.